2019
DOI: 10.1159/000502915
|View full text |Cite
|
Sign up to set email alerts
|

Personalised Nutrition Technologies and Innovations: A Cross-National Survey of Registered Dietitians

Abstract: Background: Commercial technology-enabled personalised nutrition is undergoing rapid growth, yet its uptake in dietetics practice remains low. This survey sought the opinions of dietetics practitioners on personalised nutrition and related technologies to understand the facilitators and barriers to its application in practice. Method: A cross-section of registered dietitians were recruited in the USA, UK, Australia, Canada, Israel, Mexico, Portugal, Spain, and South Africa. The questionnaire sought their views… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
1
4
0
1
Order By: Relevance
“…All informants have not applied this knowledge in their workplace using actual procedures. This is in line with Abraham et al (2019) that the application of genebased nutrition services throughout the dietetics profession is low 13 . Some informants (4 out of 7 informants) stated that the application can be done by providing education about gene-related diseases during counseling.…”
Section: Application Of Nutritional Genomics In Hospitalssupporting
confidence: 90%
See 2 more Smart Citations
“…All informants have not applied this knowledge in their workplace using actual procedures. This is in line with Abraham et al (2019) that the application of genebased nutrition services throughout the dietetics profession is low 13 . Some informants (4 out of 7 informants) stated that the application can be done by providing education about gene-related diseases during counseling.…”
Section: Application Of Nutritional Genomics In Hospitalssupporting
confidence: 90%
“…genetic testing, test reliability, scientific validity, clinical utility, and efficacy of this new technology 13 .…”
Section: Gambaran Pengetahuan Ahli Gizi Tentang Pelayanan Gizi Berbas...mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, since 2017, dietitians in the UK have had access to free, on-demand webinars for patients (www.patientwebinars.co.uk) as part of their treatment and/or education regarding certain gastroenterological conditions [5]. On the other hand, a 2019 survey by Abrahams et al [6] demonstrated that most dietitians did not consider technology to play an important role in their current practice. The most important reasons for this were fear of the profession losing value and lack of financial standards while the unsystematic approach may not have a lasting effect on patients.…”
Section: Future Perspectives Of Dietetic Practicementioning
confidence: 99%
“…Although dietitians typically use face-to-face consultations, patients may be more interested in technology-assisted consultations (13) . A 2019 survey by Abrahams et al (14) demonstrated that most dietitians did not consider technology to play an important role in their current practice. This may be the result of a lack of e-readiness (15) , training and professional development, remuneration, or exposure to the opportunities that it provides to enhance the efficiency and delivery of patient-centred care (11) .…”
Section: Dietetics In the Digital Worldmentioning
confidence: 99%